2008
DOI: 10.1097/mph.0b013e3181758947
|View full text |Cite
|
Sign up to set email alerts
|

XLA-associated Neutropenia Treatment

Abstract: X-linked agammaglobulinemia (XLA) is a primary B-cell deficiency syndrome with an incidence of 5 to 10 cases per million. The current treatment approach includes intravenous immunoglobulin and aggressive antibiotic regimens for infections. Besides recurrent infections, XLA patients may present with other manifestations, such as alopecia, enteropathy, amyloidosis, and neutropenia. Neutropenia, which has been shown in up to 25% of affected patients, might also contribute to the degree of severity of bacterial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In Africa, diarrhea was more common than in European cohorts with nearly half of the patients with chronic diarrhea 8 . Less frequently reported complications of XLA include neutropenia, usually with Pseudomonas infection at the time of diagnosis, and the devastating enteroviral meningoencephalitis 20, 21. Some manifestations may be associated with delay in diagnosis, however, differences in infection pattern may also be related to regional variation in exposure 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, diarrhea was more common than in European cohorts with nearly half of the patients with chronic diarrhea 8 . Less frequently reported complications of XLA include neutropenia, usually with Pseudomonas infection at the time of diagnosis, and the devastating enteroviral meningoencephalitis 20, 21. Some manifestations may be associated with delay in diagnosis, however, differences in infection pattern may also be related to regional variation in exposure 22 .…”
Section: Introductionmentioning
confidence: 99%
“…While many PIDDs, in particular common variable immune deficiency (CVID), chronic granulomatous disease (CGD), Wiskott Aldrich Syndrome (WAS), Immunodysregulation, Polyendocrinopathy, Enteropathy, X-linked syndrome (IPEX), and the Hyper IgM Syndromes, are often associated with a variety of autoimmune conditions and/or formation of autoantibodies [5, 6], subjects with XLA, on adequate immunoglobulin replacement, are generally considered to be spared these inflammatory conditions and have a good quality of life [7]. Patients with XLA, especially at the time of diagnosis and in association with acute infections, may have neutropenia; however, overall, other cytopenias have not been reported and the neutropenia is not thought to be autoimmune in nature [8]. Early reports of arthritis in XLA patients are now often ascribed to mycoplasma or other infections, likely due to insufficient immune globulin treatment [3, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Although patients with XLA are generally considered to have a low risk of autoimmune or inflammatory diseases compared with other PID patients, evidence from survey studies suggests that some XLA patients show symptoms with similar diagnostic features to RA, IBD, or other conditions, including alopecia, enteropathy, AIHA, ITP, neutropenia, and Kawasaki disease [55,56,57]. It has been reported that 21% of XLA patients show symptoms of chronic diarrhea; however only 4% of them are diagnosed with Crohn's disease [56].…”
Section: Autoimmunity In Padsmentioning
confidence: 99%